2011
DOI: 10.1111/j.1600-0838.2011.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic recovery following sprint interval exercise

Abstract: The autonomic nervous activity was assessed following supramaximal exercise through heart rate (HR) and blood pressure (BP) variability (HRV and BPV) and baroreflex sensitivity (BRS). The beat-to-beat HR and BP were recorded during the supine and standing states before (PRE) and at 60 (R60) and 120 min (R120) following single (one Wingate, 1W) and multiple sprint intervals (four Wingates interspersed with 4 min of light cycling, 4W). The supine low frequency (LF) component was increased (P<0.001) and the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 28 publications
10
58
0
1
Order By: Relevance
“…10.3 ± 2.6 and 9.2 ± 2.0 mmol/L for male and female Italian Olympic judoist [13], 10 mmol/L [42], or 12.3 ± 0.8 mmol/L [43]; and just a bit under lactate productions reached in real competition (13.4 ± 5.2 mmol/L in the first contest in an international judo tournament) [44]. However, although [LA] peak during recovery from the BSJT test was also similar to those previously reported following usual running supramaximal intermittent protocols [4,9], it seemed slightly lower compared to those measured after repeated Wingate test [45,46]. Considering that the abovementioned studies were carried out with recreational athletes, which are known to reach lower [LA] peak levels after supramaximal exercises [15,46], our lactate results seem even lower.…”
Section: Discussionsupporting
confidence: 57%
“…10.3 ± 2.6 and 9.2 ± 2.0 mmol/L for male and female Italian Olympic judoist [13], 10 mmol/L [42], or 12.3 ± 0.8 mmol/L [43]; and just a bit under lactate productions reached in real competition (13.4 ± 5.2 mmol/L in the first contest in an international judo tournament) [44]. However, although [LA] peak during recovery from the BSJT test was also similar to those previously reported following usual running supramaximal intermittent protocols [4,9], it seemed slightly lower compared to those measured after repeated Wingate test [45,46]. Considering that the abovementioned studies were carried out with recreational athletes, which are known to reach lower [LA] peak levels after supramaximal exercises [15,46], our lactate results seem even lower.…”
Section: Discussionsupporting
confidence: 57%
“…In this context, Buchheit et al (2007a) provided a strong rationale for using RS training, including (1) higher compatibility with Western society's time-poor lifestyle, (2) higher attractiveness for sedentary individuals, and (3) maintenance or increase in muscular strength. Several studies have reported, however, that short-term parasympathetic reactivation is impaired after RS running (Buchheit et al 2007a;Nakamura et al 2009;Niewiadomski et al 2007;Stuckey et al 2012), with only one study reporting any effect of a 9-week RS training programme on trained male adolescents (Buchheit et al 2008). To the best of our knowledge, no study to date has analysed the impact of adding RS training to the daily activities of healthy adults on postexercise autonomic function.…”
Section: Perspective and Practical Applicationsmentioning
confidence: 74%
“…As such, it is considered a reliable way to induce metabolic adaptations in human skeletal muscle Girard et al 2011). Studies analysing the effects of RS exercise on postexercise PNS r have found it to be highly impaired (Buchheit et al 2007a;Nakamura et al 2009;Niewiadomski et al 2007;Stuckey et al 2012) due to the anaerobic processes involved in this type of exercise (Buchheit et al 2007a). Indeed, it is widely recognised that a lower level of PNS r after RS is related to the heightened sympathetic activity that occurs during RS exercise (Ray and Hume 1998) and to the persistent elevation of adrenergic factors (Hagberg et al 1979) and of local metabolites during recovery (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Kemi and Wisløff (2010) describes high-intensity interval training (HIIT) as an exercise training method that is characterized by short (10 s to 5 min), repeated bouts of vigorous activity, executed at or near peak oxygen uptake, and interspersed by periods of rest or low-intensity exercise. The idea behind HIIT is to allow the physiological systems to be overloaded with exercise intensities greater than those achieved during a progressive maximal aerobic capacity test (Stuckey et al 2011) by separating the work done in rest intervals (Kemi and Wisløff 2010). HIIT has been described as a time-efficient training strategy which could serve as motivation for individuals who claim lack of time as the major reason for not adhering to a training regime.…”
Section: Introductionmentioning
confidence: 99%